The Effect of Organizational Culture and Leadership on Employee Performance with Motivation as a Mediating Variable in the Era of Industry 4.0 at PT.Toray International Indonesia - Toni Ardhi Wiansyah (Madani Connection, 2024)
This study aims to 1) analyze the influence of organizational culture and leadership on employee motivation of PT Toray Internasional Indonesia. 2) analyze the influence of organizational culture and leadership on employee performance of PT Toray Internasional Indonesia. 3) analyze the effect of work motivation on employee performance of PT Toray Internasional Indonesia. 4) To analyze the influence of organizational culture and leadership on employee performance through work motivation. The research was conducted at PT Toray Internasional Indonesia with a research sample of 52 respondents. The sampling technique used saturation technique. The data analysis method uses path analysis. The results showed that: 1) there is a positive and significant influence both partially and simultaneously between organizational culture and leadership on employee motivation, 2) there is a positive and significant influence both partially and simultaneously between organizational culture and leadership on employee performance, 3) there is a positive and significant influence between motivation on employee performance, 4) organizational culture and leadership factors affect employee performance through motivation within PT Toray Internasional Indonesia. This also states that the work motivation factor functions or acts as an intervening variable.